Fenomena Phubbing: Peran Teknologi Komunikasi Dalam Perubahan Interaksi Sosial - Sitorus, Hema Junaice; ., Irwansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The rapid advances in communication technology have an impact on our daily lives, careers, and modes of communication. IoT (Internet of Things), e-learning, AI (Artificial Intelligence), cloud computing, mobile apps, virtual reality (VR), and augmented reality (AR) communication are some of the key aspects in the development of communication technology. These trends explain how advancements in communication technology could impact daily interactions and lifestyle choices. Even while these developments create opportunities for efficiency and connectivity, it's essential to understand and deal with the societal problems and consequences that these developments also bring with it. Phubbing has become a thing as a consequence of technology use gone wrong. "Phubbing" is the practice of someone spending excessive amounts of time, especially during social interactions, attached to an electronic gadget, such as a smartphone. The goal of this research is to determine how phubbing affects social relationships and how advancements in technology contributed to this trend. Media Dependency Theory and Media Equation Theory analysis are used to support this research, which uses a qualitative literature review approach from multiple relevant journals. The findings of this study demonstrate that the phenomenon of phubbing and its effects on social interaction are the outcome of media dependency caused by technological advancements.